Analysis Effectiveness Fund Management and Accuracy Target Distribution of Zakat in Increase Empowerment Mustahik : Study on BAZNAS Siak Regency - Safrizal Safrizal; Novita Diah Ramadhani; Miftahul Miftahul; Ramadahniel Islami (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2026)
This study aim for analyze effectiveness zakat fund management and accuracy target distribution of zakat in increase empowerment Mustahik at the National Zakat Agency (BAZNAS) of Siak Regency. Effective zakat management and appropriate distribution target become factor important in realize the function of zakat as instrument empowerment economy public as well as alleviation sustainable poverty. Research​ use approach qualitative with method studies case. Data collected through interview in-depth, observation, and documentation. Informants study chosen use purposive sampling technique, which consists of on leaders and managers of BAZNAS Siak Regency and mustahik recipient benefits of the zakat program. Data analysis was carried out using the encompassing Miles, Huberman, and Saldaña model data reduction, data presentation, and data extraction conclusion, whereas data validity is tested through triangulation sources and triangulation technique. Research results show that management of zakat funds at BAZNAS Siak Regency has implemented in a way planned , transparent and accountable through stages collection , distribution and utilization in accordance with applicable provision.​ Distribution of zakat has been apply mechanism verification based on eight groups (asnaf) so that assistance provided​ relatively appropriate target, although Still there is constraint in the form of limitations number of amil and the extent of the service area. Empowerment program mustahik implemented through help consumptive and productive, such as the Siak Sejahtera Program, Z-Mart, Z-Chicken, and assistance farm cows. These programs give impact positive to improvement ability economy, independence business, as well as welfare mustahik